An Efficient Approach for Image Retrieval using Particle Swarm Optimization - Kurchaniya, D; Johari, PK (International Journal of Computer Sciences and Engineering, 2025)
Image retrieval systems are used to search and browse the images from large digital image databases and retrieval of these images. Content-Based Image Retrieval (CBIR) gives an efficient approach to browse and retrieve images from these large databases, but the semantic gap between low-level and high-level features is a big issue. To overcome this issue Particle Swarm Optimization is used with a new combination of low-level features. Moments can be used to characterize the color distribution of an image. A color feature of an image is extracted by calculating color moments which are unique and invariant to rotation and scaling. Rotated Local Binary Pattern is used to extract texture information from the image, it is invariant to rotation and scaling. Edges give the object representation of an image and used as a feature descriptor for image retrieval, Here Edge Histogram Descriptor is used to find out the abruptly changes in the pixel value of the image. Edge Histogram Descriptor (EHD) provides the spatial information about five types of edges of an image. For performance evaluation, we simply used weighted Euclidian distance with optimal weights and calculate Average precision, recall and accuracy. Experiment result shows that the proposed method gives improved precision and recall in comparison to existing method. The efficiency of proposed system is tested for three types of datasets: WANG dataset, LI dataset and Caltech-101 image dataset.